Pengaruh Media Gambar terhadap Kemampuan Menyusun Teks Prosedur oleh Siswa Kelas VIII SMP PGRI 3 Medan - Tri Indah Prasasti (Medan Resource Center, 2022)
This research aims to find out the influence of image media on the ability to compile the text of the procedure of students of class VIII PGRI 3 Medan Junior High School. The method used is the experimental method. The tool or instrument used is a test to arrange the text of the procedure in sequence and logical. Students who received treatment using image media were categorized as